2020
DOI: 10.1038/s41598-020-61759-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Pancreas Volume Measurements Using MRI

Abstract: Reduced pancreas volume, as measured by non-contrast magnetic resonance imaging (MRi), is observed in individuals with newly-diagnosed type 1 diabetes (T1D) and declines over the first year after diagnosis. in this study, we determined the repeatability and inter-reader reproducibility of pancreas volume measurements by MRI. Test-retest scans in individuals with or without T1D (n = 16) had an intraclass correlation coefficient (ICC) of 0.985 (95% CI 0.961 to 0.995) for pancreas volume. Independent pancreas out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…The deep learning-based segmentation calculated smaller pancreas volume in individuals with T1D, in agreement with previous studies using manual segmentation [1][2][3], but absent the subjectivity inherent to manual segmentation. In fact, the agreement between deep learning and manual pancreas segmentation in this study outperformed the agreement between two different readers performed using images derived from the same study [17]. This finding highlights the subjectivity in manual pancreas segmentations which are in turn used to train deep learning models.…”
Section: Discussionsupporting
confidence: 50%
“…The deep learning-based segmentation calculated smaller pancreas volume in individuals with T1D, in agreement with previous studies using manual segmentation [1][2][3], but absent the subjectivity inherent to manual segmentation. In fact, the agreement between deep learning and manual pancreas segmentation in this study outperformed the agreement between two different readers performed using images derived from the same study [17]. This finding highlights the subjectivity in manual pancreas segmentations which are in turn used to train deep learning models.…”
Section: Discussionsupporting
confidence: 50%
“…For example, a meta-analysis of pancreatic volume and fat content found high heterogeneity between studies [ 28 ]. However, we found that MRI of the pancreas performed at a single site is repeatable [ 29 ]. The choice of image acquisition and processing parameters can influence a calculated measure, as previously demonstrated in pancreatic measurements of fat fraction [ 30 ], T1 [ 31 ] and ADC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation of this study is the use of a single reader to outline all pancreas images in this study. The use of multiple readers may lead to variation in MRI measurements of the pancreas [ 29 ]. Magnetic resonance elastography is another promising technique for assessing the pancreas, but as it requires specialized hardware and software not available at our study sites it was not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreas borders can be difficult to delineate, which may lead to reader subjectivity in pancreas volume measurements. However, reproducibility across multiple readers reveals good agreement between two readers outlining the same image (24,25). One caveat is that pancreas volume changes over the course of the human lifespan in the absence of disease, with rapid increases in size over childhood and pancreas atrophy in later life (14).…”
Section: Pancreas Volumementioning
confidence: 93%
“…Porcine pancreas volume calculated from MRI demonstrated excellent correlation with gold standard water displacement measurements (23), indicating the accuracy of the technique. Furthermore, in human subjects who received MRI scans in quick succession, measurements of pancreas volume were highly repeatable (24,25). Pancreas borders can be difficult to delineate, which may lead to reader subjectivity in pancreas volume measurements.…”
Section: Pancreas Volumementioning
confidence: 99%